“A Lot Has Become Muted:” Supporting LGBTQ+ Students Living at Home During the Covid-19 Pandemic (Comparative & International Education Series, 2021)
In this chapter, we explore the unique experiences faced by students who are members of the LGBTQ+ community after returning home when postsecondary campuses closed due to the Covid-19 pandemic in the spring of 2020.  Using the case study method, we present challenges that students faced when navigating the campus housing closure, living at home with family members, and finding support remotely.  We offer implications for future policy and practices related to students who are members of the LGBTQ+ community on campus and in the instance of emergency campus closure in the future.